Mediastinal infections: diagnostic and therapeutic advances from traditional surgery to novel minimally invasive techniques - Xu, Yansong; Liang, Guanbiao; Huang, Chanyu; Wang, Yuewu; Liang, Zheng; Jiang, Yun; Huang, Cuiqing; Liu, Junting (Frontiers in Medicine, 2025)
Mediastinal infections present significant diagnostic and therapeutic challenges, contributing to highly variable mortality. Diagnostic dilemmas arise from complex anatomy and radiographic similarities to malignancies. Endobronchial Ultrasound-guided Transbronchial Needle Aspiration (EBUS-TBNA) and cultures are constrained by small samples, architectural distortion, low sensitivity, and slow results in special circumstances. Therapeutic obstacles include antibiotic resistance, poor antimicrobial penetration due to altered vascularity, and high surgical morbidity. Endobronchial ultrasound-guided transbronchial mediastinal cryobiopsy (EBUS-TMC) provides larger histologically preserved specimens; metagenomic next-generation sequencing (mNGS) achieves rapid sensitive pathogen detection; advanced imaging (Dual Energy Computed Tomography, DECT; Positron Emission Tomography/Computed Tomography, PET/CT) enhances lesion differentiation and intervention planning; while minimally invasive drainage, nanocarrier-based targeted antimicrobial delivery, and reconstructive techniques collectively reduce complications and improve therapeutic efficacy. Multidisciplinary integration of these innovations is advancing precision medicine approaches.